Isaiah Thomas's Massachusetts, Connecticut, Rhode Island, Newhampshire & Vermont Almanack, With an Ephemeris, for the Year of our Lord 1800: Being the IVth after Bissextile, or Leap Year, and 24th of Columbian Independence. - Thomas, Isaiah, 1749-1831. (Tufts University. Tisch Library., 2018)
24 leaves. Tisch Library copy contains handwritten annotations.